Philosophical foundations for informing the future(S) through IS research. Issue 3 (4th May 2018) - Chiasson, Mike; Davidson, Elizabeth; Winter, Jenifer
Abstract: Information systems (IS) scholars have suggested IS researchers have a responsibility to consider how information and communication technologies could, in the future, influence sociotechnical practices and outcomes. However, research focused specifically on "the future" has yet to gain a strong foothold within the scholarly IS field. In this essay, we suggest a philosophical foundation and epistemological basis for futures-oriented research to advance such scholarship in the IS field. We first highlight epistemic assumptions about futures-oriented research drawn from the discourse of futures studies. We then draw on Feenberg's philosophy of "potentiality and actuality" of technology as a foundation to consider how knowledge generated through IS research about the sociotechnical past and present might inform futures-oriented inquiry. We illustrate these arguments with examples from the emerging arena of "big data" research.